A intertextualidade de Edgar Morin - Ramos, Roberto (Revista Latinoamericana de Metodología de las Ciencias Sociales.)
The texts of Edgar Morin, implicitly and explicitly, they bring different philosophical influences. They have a drive through the design of the Paradigm of Complexity. This intertextuality is the object of study of this test, a qualitative approach and transdisciplinar, so we can understand the characteristics of complex knowledge and their respective production